Naming, meaning, objects of the world in “Philosophical investigations” by Ludwig Wittgenstein - Laktionova, Anna (Sententiae, 2011)
In Wittgenstein’s “Philosophical Investigations” linguistic meanings of the names used in language games discover the forms of life as portions of reality which represent objects of the world. In the “Tractatus Logico-Philosophicus” they, as well as meanings, senses, contents of linguistic expressions, correspond to the facts (states of affairs) established in empirical experience. Contrasting of different periods of Wittgenstein’s legacy is not justified.